Pengaruh Faktor Sosial Ekonomi Dan Kompetensi Manajerial Peternak Sapi Perah Terhadap Pendapatan (Suatu Kasus Pada Peternak Sapi Perah di KPSBU Lembang di Kecamatan Lembang, Kabupaten Bandung Barat) - Euis Dasipah; Karyana KS; Dety Sukmawati; Ida Danah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
The research has aim at to know relationship between the socio economic factors and managerial competence and and it’s infuence to the breeder’s income. The method was used by survey technique toward the breeders. The Sampling technique was used by simple random sampling method by using slovin formula, carried out 70 units. The data was analyze by the path analyze to verify the hypothesis. The result of the research that was the relationship strongly between the influence of socio economic factors and managerial competence shown by the coeficient of corellation r = 0,77. The economic factors has the indicators : age, formal education, knowledge, experience, dependency ratio, motivation of business and scale of business has gained 78,53% citeria good. Managerial competence of breeder has indicators: data recording, milking technique , livestock health, feed, mating,cowshed, man power and marketing obtained 78,94 %, criteria good. The socio economic factors and managerial competence of breeder give a positive influence to the breeder income. The contribution of managerial competence shown greater than The socio economic factors. Each other contribution are 33,11 % and 20,70 %.